Evaluation of Pre-operative Biopsy, Surgical Procedures and Oncologic Outcomes in Upper Tract Urothelial Carcinoma (UTUC) - Koll, Florestan J.; Meisenzahl, Eva; Haller, Bernhard; Maisch, Philipp; Kirchhoff, Florian; Horn, Thomas; Gschwend, Jürgen E.; Schmid, Sebastian C. (Frontiers in Surgery, 2021)
Purpose: Discordance between preoperative biopsy and final pathology for Upper Tract Urothelial Carcinoma (UTUC) is high and optimal management remains controversial. The aim of this study is to evaluate the accuracy of preoperative biopsy, to identify prognostic factors and to evaluate the effect of adjuvant chemotherapy on survival and oncologic outcome in UTUC. Methods: We analyzed records of patients receiving surgical treatment for UTUC. Pathology of preoperative biopsy was compared to surgical specimen. We used Kaplan-Meier method to estimate survival probabilities and Cox’s proportional hazards models to estimate the association between covariates and event times. Primary endpoint was overall survival (OS). A matched-pair analysis was performed to evaluate the effect of adjuvant chemotherapy. Results: 151 patients underwent surgical treatment (28% open, 36% laparoscopic, 17% robotic radical nephroureterectomy; 14% segmental ureteral resections and 5% palliative nephrectomy) for UTUC and were included in the analysis. Upstaging from